Marion and the secret letter - Barkley, Callie (Barkley, Callie. Critter Club, 2017)
Taking a turn caring for the class pet hamster, Marion is devastated when the hamster goes missing and she receives an anonymous letter in her locker with clues leading to a mysterious scavenger hunt.